PENGARUH KOMPOSISI DAN UKURAN SERBUK KULIT KERANG DARAH (ANADORA GRANOSA) TERHADAP KEKUATAN TARIK DAN KEKUATAN BENTUR DARI KOMPOSIT EPOKSI-PSSERBUK KULIT KERANG DARAH - Addriyanus; Tommy; Halimatuddahliana (Jurnal Teknik Kimia USU, 2015)
This study was aimed to investigate the effect of filler content and particle size of cockle-shell powder in tensile strength and impact strength of epoxy-PS composite. Epoxy resin was used as matrix, polyaminoamide as hardener, cockle-shell powder as reinforcement, polystyrene as toughening agent and chloroform as solvent. Filler content was varied from 10-50% and the macro particle was varied from 50-260 mesh. The composite was prepared by using compression moulding, then tensile test and flexural test were done. The results showed that addition of cockle-shell powder improved both tensile strength and impact strength of the composite. Addition of 30% (wt) reinforcement with 200 mesh particle size had given maximum tensile strength of 5,50 MPa and maximum impact strength of 30044,3 J/m2.